Self-service data analytics and governance for managers - Myers, Nathan E.; Kogan, Gregory (Hoboken, New Jersey : John Wiley & Sons, Inc., 2021)
"Decentralization of data analytics tools has created a new digital environment in the finance and accounting world. With users performing their own analysis on data sets, there are important governance techniques to maintain process control in the new environment. While much has been written about data analytics capabilities, the treatments tend to either introduce and train users on used in data analytics. Prominent data analytics tools and capabilities for finance and accounting will be introduced. The authors will provide much-needed context to show where key tools can be deployed. Most important, managers must be equipped to structure the inevitable chaos that can result from putting tools into the hands of end-users. This book is meant to fill this gap and provide the reader with deployment and governance frameworks to promote data analytics capabilities on a large scale. In addition, the authors will clarify the capabilities of analytics tools in the accounting and finance world (based on real world scenarios). This book will focus on how finance, accounting, and operations teams need to adapt to the new digital environment. Readers will be presented with chapters building tool familiarity, matching tools with common use cases, and managing tool deployment in a way that ensures control and stability and ultimately high-quality digital outputs. Significant focus will be dedicated to establishing process governance standards as self-service digital tooling makes its way throughout an organization and teams."--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on June 02, 2021).
John Wiley and Sons
Keywords: Accounting -- Data processing; x; Accounting -- Data processing